POLITICAL PROCESSES IN TURKEY IN 1917, THE ESTABLISHMENT OF THE SOVIET AUTHORITY IN THE COUNTRY AND THE FORMATION OF THE COUNCIL OF PEOPLE'S COMMISARS - MAKHMUDOV KOMAL SAMADOVICH (Scholar Express Journals, 2023)
The reasons for the huge losses in the fields of the first World War, the disadvantaged situation in the colonial and dependent territories, the economic tension in the central regions of Russia, the collapse of the entire Russian Empire of the 1917s into the domain of revolutionary-political processes are covered. On February 28, 1917, the revolutionary events in Petrograd show the history of the capture of the Petropavlovsk fortress and the Winter Palace and the processes of imprisonment of Ministers of the imperial government, the collapse of the absolute monarchy in the Russian Empire as a result of the February Revolution and the overthrow of the Romanov dynasty, which had ruled the state for three centuries. The reasons for the fact that these processes also made a sharp twist in the socio-economic and political events of the Turkestan territory in 1917 are highlighted.
Keywords: Duma; Committee; ISS; commissar